PENGARUH LATIHAN SHOOTING DENGAN MENUNGGU GILIRAN TERHADAP AKURASI SHOOTING TEAM SEPAKBOLA SMK NEGERI 1 KANDIS - Riyanto, Dory; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study is to determine the effect of shooting training by waiting their turn on the shooting accuracy of the SMK N 1 Kandis football team. This research was conducted at the soccer field in Rokan village, Kandis sub-district in October - December 2019. This study used a one-group pretest-posttest design approach with a sample of 16 people. After conducting research that was started from the initial data collection (Pree-test), the calculation resulted in a Lhitung of 0.1796 and a Ltable of 0.213, it can be concluded that the results of the pree-test were normally distributed and from the final data collection (Post-test) a calculation was carried out that resulted Lhitung of 0.2022 and Ltabel of 0.213 can be concluded that post-test results data are normally distributed. Then based on the analysis of t test results obtained tcount of 7 and ttable of 1.75 then H0 is rejected and H1 is accepted.Key Words: Shooting, Waiting Turn, Accuracy